The Effect of the Addition of Virgin Coconut Oil (Vco) on the Physical Stability of Carrot Sunscreen Preparations (Daucus carota L.) - Kalsum, Ummi; Nihlatunnaja, Nadiya; Firstca Aulia Rachma (Science and Community Pharmacy Journal, 2023)
UV rays have harmful side effects of free radicals, dry skin can reduce the body's defenses against the effects of free radicals, antioxidants have activity as a free antiradical, Carrots have antioxidant activity due to the presence of carotenoid compounds, Fatty acid content from VCO which has the function of softening and moisturizing the skin.This study aims to determine the effect of the addition of Virgin Coconut Oil (VCO) on physical stability in the formulation of carrot sunscreen cream preparations. As well as Knowing the effectiveness of antioxidants on carrot tubers. Research methods test the physical characteristics of the preparation (organoleptic, pH, homogeneity, adhesion and dispersion), Cycling test cream stability test and in the onewayanova test.The results of the study obtained the influence of the stability of oily texture and rancid odor in formula III (21%) and based on data analysis, the higher the concentration, the wider the distribution power of the preparation and the decrease in the adhesion of the preparation. Conclusion The addition of Virgin Coconut Oil (VCO) affects the stability of texture and smell in formula III (21%) and based on data analysis the addition of Virgin Coconut Oil (VCO) to carrot sunscreen cream (Daucus carota L.) the higher the concentration the wider the dispersal power of the preparation and the decrease in adhesion of the preparation.